Identifying high-yielding and drought-tolerant wheat cultivars based on ideotypic traits and yield responses to stress - Yibo Li; Fulu Tao; Yuanfeng Hao; Yonggui Xiao; He Zhonghu; Reynolds, Matthew P. (Wiley, 2024)
Drought is one of the most adverse factors affecting plant growth and productivity. Identifying elite genotypes and their ideotypic traits conferring high yield potential and drought tolerance is critical in selecting and breeding drought-tolerant wheat cultivars. In this study, we conducted field experiments at the Xinxiang Agricultural Comprehensive Experimental station in the North China Plain from 2018 to 2020 and assessed 209 wheat cultivars released since the 1940s under irrigated and nonirrigated conditions. Then, we selected drought-tolerant cultivars by classifying them into four groups based on yield response to drought stress and several drought indices. Finally, the key ideotypic traits associated with high yield potential and drought tolerance were identified. Results indicated that the grain yield of the 209 cultivars decreased on average by 10.4% and 9.4% under nonirrigated treatment in 2018-2019 and 2019-2020, respectively, relative to full irrigation. The high-yielding cultivars under both irrigation treatments are characterised by a compact plant type, larger thousand-grain weight, larger chlorophyll content, higher leaf photosynthesis, shorter plant height and stay-green traits. The stomatal and nonstomatal limitations are strongly associated with genotype yield performance, elucidating a potential mechanism underlying drought tolerance. Drought tolerance and yield stability of wheat cultivars have been improved through breeding over the past 70 years. Our findings enhance understanding of drought tolerance and identify genotypes and traits beneficial for breeding high-yielding and drought-tolerant cultivars.